2023
DOI: 10.1039/d3cc00262d
|View full text |Cite
|
Sign up to set email alerts
|

Modular enhancement of circularly polarized luminescence in Pd2A2B2 heteroleptic cages

Abstract: Metal-mediated assembly allows to combine an achiral emissive ligand A with different chiral ligands (such as B) in a non-statistical fashion, obtaining Pd2A2B2 heteroleptic cages showing circularly polarized luminescence (CPL)....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Studies have been also performed using organic emitting chromophores as building block for CSC. Clever reported a Pd 2 L 4 CSC, based on chiral helicene ligand and a fluorenone based emissive ligand (| g lum | up to 0.0025) [55,56] . Interestingly, the flexibility of 16 upon encapsulation of anionic molecules, an achiral bis‐sulfonate guest 17 , provided a changing in CPL output, leading to a bathochromic shift and signal amplification (4 fold increase of | g lum |) (Figure 8).…”
Section: Novel Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have been also performed using organic emitting chromophores as building block for CSC. Clever reported a Pd 2 L 4 CSC, based on chiral helicene ligand and a fluorenone based emissive ligand (| g lum | up to 0.0025) [55,56] . Interestingly, the flexibility of 16 upon encapsulation of anionic molecules, an achiral bis‐sulfonate guest 17 , provided a changing in CPL output, leading to a bathochromic shift and signal amplification (4 fold increase of | g lum |) (Figure 8).…”
Section: Novel Optical Propertiesmentioning
confidence: 99%
“…Pd 2 L 4 CSC, based on chiral helicene ligand and a fluorenone based emissive ligand (j g lum j up to 0.0025). [55,56] Interestingly, the flexibility of 16 upon encapsulation of anionic molecules, an achiral bis-sulfonate guest 17, provided a changing in CPL output, leading to a bathochromic shift and signal amplification (4 fold increase of j g lum j) (Figure 8). This example showed that only the combination of three elements, imparted chirality from ligand 15, emissive properties from ligand 14, and Pd cations to create the void cavity, could contribute to achieve novel properties that could not otherwise be obtained with the single components.…”
Section: Minireviewsmentioning
confidence: 99%
“…[43] Pd 2 L 4 CSC, based on chiral helicene ligand and a fluorenone based emissive ligand (j g lum j up to 0.0025). [55,56] Interestingly, the flexibility of 16 upon encapsulation of anionic molecules, an achiral bis-sulfonate guest 17, provided a changing in CPL output, leading to a bathochromic shift and signal amplification (4 fold increase of j g lum j) (Figure 8). This example showed that only the combination of three elements, imparted chirality from ligand 15, emissive properties from ligand 14, and Pd cations to create the void cavity, could contribute to achieve novel properties that could not otherwise be obtained with the single components.…”
Section: Novel Optical Propertiesmentioning
confidence: 99%
“…This allows concomitant bond cleavage and formation, which leads to the development of thermodynamically stable product(s). 26,27 The coordination-driven self-assembly field has evolved over the years, starting from the seminal work by Lehn 28 and Sauvage 29 to develop metal-organic helicates, [30][31][32] catenates, [33][34][35] grids, 36 knots 37,38 and rotaxanes. [39][40][41] The coordination-driven approach is high-yielding, and the ease of such synthesis has led to the development of a plethora of assemblies.…”
Section: Introductionmentioning
confidence: 99%